Pengembangan E-Module Aplikatif untuk Memperkuat Penguasaan Materi Fisika pada Kompetensi Keahlian di SMK - Basyaruddin, Irfan; Ellianawati, Ellianawati (UPEJ Unnes Physics Education Journal, 2021)
Physics is the main subject given to Vocational High Schools (SMK), especially in the fields of technology and engineering. The implementation of the 2013 curriculum at the vocational education level has an impact on changing the time for learning physics to become relatively narrow. This is added with the covid-19 pandemic, which requires students to learn independently, it makes teacher experience difficulty in delivering physics material as a whole and in-depth. The purpose of this research is to develop an applicative electronic module (E-Module ) based on android as a supplement in learning that can be used by students independently. The method used is Research and Development (RnD). The sample in this study were students of class X TKR 2 and X TKR 3 at SMK Muhammadiah Randublatung. The results of the feasibility test show that the E-Module is suitable for use as a supplement in learning with a percentage of eligibility for the material of 84.72% and a percentage of media feasibility of 95%. The legibility test results showed that the E-Module was easily understood by students with a percentage of 82%. The results of the field test showed that the E-Module got a good response from students as a supplement in learning with a percentage of 80.20%.